2011
DOI: 10.5866/3.3.635
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioma of Tongue: A Rare Entity

Abstract: Lymphangiomas are uncommon congenital malformations of lymphatic vessels filled with a clear protein-rich fluid containing few lymph cells. They result from abnormal development of lymphatic system with obstruction to lymph drainage from the affected area. Herewith, we present an interesting case of lymphangioma of the tongue in a 13-year-old boy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 6 publications
(14 reference statements)
0
30
0
1
Order By: Relevance
“…The definition of lymphangioma, first described in 1828 by Redenbacher (apud Martinot, 1997), still controversial today. They neither become malignant nor have a familial tendency [6]. Lymphangiomas are believed to arise from lymph sac sequestration and enlarge due to inadequate drainage, from lack of communication with the central lymphatic channels or excessive secretion of lining cells [7] [8].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of lymphangioma, first described in 1828 by Redenbacher (apud Martinot, 1997), still controversial today. They neither become malignant nor have a familial tendency [6]. Lymphangiomas are believed to arise from lymph sac sequestration and enlarge due to inadequate drainage, from lack of communication with the central lymphatic channels or excessive secretion of lining cells [7] [8].…”
Section: Discussionmentioning
confidence: 99%
“…They most likely represent developmental malformations that arise from sequestrations of lymphatic tissue that do not communicate normally with the rest of the lymphatic system [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Like our case, oral lymphangioma occurs frequently on anterior two-thirds of the tongue with superficial location and pebbly surface. However, deeply located lesions were also reported that cause diffuse swelling, termed macroglossia [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiomas are hamartomatous, congenital malformations of the lymphatic system. [ 5 ] They are believed to arise from lymph sac sequestration and enlarge due to inadequate drainage, from lack of communication with the central lymphatic channels or excessive secretion of lining cells. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Among these treatment modalities, surgical excision continues to be integral to management in many cases. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%